Phase retrieval with a diffractive micro lens array - Liu, Xiyuan; Brenner, Karl-Heinz (International journal of optomechatronics, 2014)
Multi-plane phase retrieval is a well established technique for reconstructing both, amplitude and phase of an object wave. This standard technique works best, if the intensity of the object wave changes rapidly along the optical axis. For slowly varying intensities, the iterative procedure may not converge at all. To overcome this limitation we combined the standard technique with a periodic phase element. We demonstrate that a binary diffractive micro lens array with overlapping aperture significantly improves the convergence of phase retrieval and thus the quality of reconstruction. Thus multi-plane phase retrieval can be applied for both rough and smooth phase distributions.
Gesehen am 14.07.2020